Industria materiilor dure animale din situl mezolitic de la Alibeg (jud. Caraș-Severin) - Mărgărit, M.; Boroneanț, A. (Materiale și Cercetări Arheologice, 2017)
The Mesolithic settlements in the Iron Gates have yielded rich assemblages of antler, bone and Sus scrofa canines, exemplified here by the site of Alibeg (Romania). These raw materials represent for the Iron Gates region, a hallmark of local Mesolithic. The typological categories identified are bevelled tools, scrapers, preforms and blanks. Debitage remains are also present, indicating on- site raw material processing. All three categories of raw materials were readily available from the animals that were killed, and analysis of the faunal remains identified a Cervus elaphus and Sus scrofa bones within the mammalian assemblage. Our study aimed to identify the transformation pattern of antler, bone and tusk and the functional marks, which could offer clues to the way in which the pieces were used. Ethnographical studies suggest wood and hide processing as the main activities performed with such tools